Analysis of The Impact of Using Artists Via Vallen As Celebrity Endorser in Online Stores on Shop Image Brands - Edy Anas Ahmadi; Ulfatul Khasanah; Rina Sulistyowati (Publisher Cv. Inara, 2021)
This study aims to determine whether there is a variable influence of Attractiveness, Credibility, and Charisma partially, simultaneously and most dominantly on the Shopee Brand Image. It is suspected that there is a significant effect partially and simultaneously, and the most influential variable is credibility. using quantitative descriptive methods. The sample was determined as many as 89 respondents. The data analysis methods used are: Validity Test, Reliability Test, Multiple Regression Analysis, Multiple Correlation Analysis, Coefficient of Determination, t test, and F test. In the Reliability Test, it is known that all items are reliable. In the Multiple Regression Analysis, the value is 3,100. If all the independent variables increase by one unit, the Brand Image increases with the value of the regression coefficient. The coefficient of determination test results showed that R2 = 0.756 contributed 75%. In the Multiple Correlation Test, it is known that each variable has a degree of closeness. The t test results show that partially there is a significant effect on the Attractiveness and Credibility variables, while the Charisma variable has no significant effect. In the F test it is known that there is a simultaneous significant effect of all independent variables on the dependent variable. The conclusion is that there is a significant effect both partially and simultaneously of the Attractiveness, Credibility, and Charisma variables on the Brand Image. The variable that has the most dominant influence is the credibility variable.